Impact of Conflict on Mental Health in Northern Ireland: The Mediating Role of Intergroup Forgiveness and Collective Guilt - Myers, E; Hewstone, M; Cairns, E (2009)
The aim of the present research was to investigate the mediating role of group-level forgiveness and guilt in the relationship between victimhood (the extent to which the conflict affected an individual's life), exposure to violence (the level of violence in their area of residence), and group identity on the one hand, and mild psychiatric morbidity on the other. Specifically the study focused on the psychological impact of the ethnopolitical conflict in Northern Ireland, utilizing people's identification with either the Catholic or Protestant community. Our results revealed that intergroup forgiveness mediated the relationship between both victimhood and group identification, as predictors, and mild psychiatric morbidity. Collective guilt, on the other hand, mediated the relationship between both exposure to violence and group identification, as predictors, and intergroup forgiveness. Overall this study shows that forgiveness and collective guilt can act as mediators in the relationship between impact of ethnopolitical conflict and mental health, at the group level, and thus demonstrates their centrality to the reconciliation process. Implications for intergroup reconciliation initiatives in Northern Ireland are discussed. © 2009 International Society of Political Psychology.